Manila autoteknika the Philippine motorsports center - Banzon, Roland Salvador A.
The manila autoteknika project is mainly about creating the ideal setting where motorsports and city living converge in one space. Currently, motorsports is slowly losing coverage in the tourism scene today. Back in the 1970's the Philippine Motorsports scene began with names like Silverio, Tuason, Isada and more. It is about creating a city for motorsports that will help sustain and promote it in the Philippines. This will also be the kick starter, as the researcher believes, of motorsports tourism in the tourism. Throughout the discourse of the project, the researcher sought out different ways to observe the motorsports scene of Metro Manila in person, through different workshops, classes and interviews, all of which comprehensively contributed to old and new found knowledge on the past, present and future of Motorsports and its needs in the country today. At the end of the research, the author was able to formulate different solutions to new problems sought during the discourse of the research. The researcher was able to see that most problems occurred mostly due to architectural needs like proper sheds and areas for designation of specialty functions needed in the motorsports industry. In the end, the author decided to design a full development that will be able to promote and sustain motorsports enthusiasm through provision of this motorsports development, called the Manila autoteknika : the Philippine motorsports center.